Interpersonal Communication Between Husband and Wife in Building a Healthy Relationship: A Case Study in Kampung Keluarga Berkualitas Serumpun, Bandung City - Mochamad Hafizh Nurhasan; Agus Setiaman; Ira Mirawati (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study discusses the interpersonal communication of married couples in building a healthy relationship by applying five aspects of interpersonal communication: openness, empathy, supportiveness, equality, and positivity. This research uses a qualitative approach with a case study method. The subjects were five married couples living in Kampung Keluarga Berkualitas Serumpun, Bandung City. Data collection techniques included in-depth interviews and literature studies. The results showed that the five aspects of interpersonal communication were consistently applied by the couples to build a healthy relationship. The Kampung KB program also played a role in creating a supportive environment for positive spousal communication. In conclusion, effective interpersonal communication is the main foundation for a healthy and harmonious marriage.